ANALISIS EFEKTIVITAS DAN EFISIENSI PENYERAPAN ANGGARAN PENDIDIKAN DAN KESEHATAN DALAM APBD KABUPATEN ACEH BESAR PADA PERIODE 2008-2012 - Murdani Murdani; Ade Suherlan (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
This study aims to analyze the effectiveness and efficiency of budget absorption level of education and health in the Budget (budget) Aceh Besar district. The analytical method used is the ratio of the effectiveness and efficiency of revenue and expenditure. The results of this study indicate that the level of effectiveness of the education budget absorption is considered ineffective. Level of efficiency in the education budget is less efficient category. The level of effectiveness of health budgets on average less effective. The level of efficiency of the health budget shows less efficient and inefficient. Factors that influence the effectiveness and efficiency of the health sector budget realization that their force major (emergency), the internal condition of the Department of Health, the process of procurement of goods and services that are not timely and not within specifications, on corruption, budget execution document and revision process, an increase in the allocation of expenditure in the Department of Health in the event of changes in the budget, lack of coordination between planning and execution, lack of health budgetsDOI: 10.15408/sjie.v3i2.2057